(untitled) (KULT_online, 2010)
Monika Margarethe Raml’s dissertation deals with artificially created human beings as they are designed by genetic engineering and narrated in contemporary literature. Prose fiction and essayistic texts are the focus of interest here. Raml’s central term, ’homo artificialis’, has a double meaning. As Raml understands it, it denominates both the person who creates artificial people – the scientist and the author of prose fiction – as well as the person created. In the first part of her dissertation, Raml presents the subject from the perspective of German philology and natural science. Then she deals with aspects of the ’homo artificialis’ in the texts chosen. Finally, the author summarises essential features of the ’homo artificialis’ and reflections on his position in society. Explanations of genre and the function of the novels in discourse on gene technology complete the book.